Value-Based Approach in Employee Recruitment and Selection in Technology-Based Companies - Helmi F Wandara; Fajariah Asmawati; M Benyamin Latucosina; Beno Ady Saputra; Putri Melina Hilery; Eric Bryan Chrisologus Sondakh; Freddy Johanis Rumambi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the application of a value-based approach in employee recruitment and selection in technology-based companies, as well as its impact on employee commitment, motivation, and retention. The background of this research is the need for technology companies to retain employees who have values aligned with the organizational culture to achieve long-term success. The method used was case studies on several leading technology companies, with interviews and surveys with employees and HR managers. The results show that a value-based approach not only improves alignment between employees and the company, but also accelerates adaptation, increases intrinsic motivation, and reduces turnover rates. Employees who share the same values with the company are more engaged in their work and more loyal to the company's goals. In conclusion, a value-based approach in recruitment and selection has proven to be effective in improving employee performance and retention in technology companies.